Assimilation Program as a Form and Form of Correctional Philosophy in Restoring Life, Life, and Livelihood for Prisoners and Realizing Community-Based Correction Institutions - Aziz Imam Hanafi; Zainal Arifin Hoesein (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Corrections play a vital role within the integrated justice system, providing a recovery process for law violators. Correctional institutions aim not only to punish but also to rehabilitate and guide offenders toward social reintegration. This study aims to evaluate the effectiveness of assimilation programs in restoring the lives and livelihoods of prisoners and to explore how correctional institutions implement community-based corrections through these programs. A qualitative research approach was employed, utilizing data from relevant journals and regulations. An empirical legal analysis was conducted to examine the impact of assimilation programs on the rehabilitation of prisoners. The findings indicate that assimilation programs significantly enhance the self-improvement and social reintegration of prisoners. These programs provide essential skills training and community engagement opportunities, which are crucial for reducing recidivism. The study concludes that assimilation programs are effective in facilitating the recovery of prisoners and promoting their reintegration into society. This underscores the need for on-going support and enhancement of such programs within correctional institutions to ensure their success and the safety of the community.